Politik cina dalam pilihan raya Dewan Undangan Sarawak 2006: manifestasi protes daripada rakyat - Lee, Kuok Tiung; Ghazali Mayudin, (Penerbit UKM, 2008)
This article discusses about the 2006 Sarawak State Assembly Election with the focus on areas which were contested by political parties representing the interest of the Chinese peopel especially Sarawak United People’s Party (SUPP) and Democratic Action Party (DAP). In this election, SUPP lost eight out of 19 seats contested. The biggest lost ever experienced by that partyu. Seven out of eight seats were won by the DAP and Parti Keadilan Rakyat (PKR). In the city area where the Chinese voters were the majority, some SUPP top leaders who held important positions in the government, lost to younger candidates from the DAP who just entered politics. The terrible defeat of the SUPP was closely related to the dissatisfaction of the voters for the failure of the SUPP to settle the problems faced by the Chinese in the city. Therefore, in Sarawak political context, the 2006 election was a protest and also a warning that the Chinese voters were ready to topple any candidates and parties that failed to safeguard and fight for their interest.